Wednesday

August 20, 2014

August 20, 2014

Posted by **rick** on Tuesday, October 5, 2010 at 2:01am.

I AM SO DAMN CONFUSED!

I tried to solve !p -> (q -> r) first

and I only got to !p -> (!q v r)

I cant see any other rule that would apply after i get that far! Someone with some knowledge please help!

- math -
**MathMate**, Tuesday, October 5, 2010 at 3:48pmYou'll need the logical equivalence:

p → q ≡ !p ∨ q

so

!p → (q→r)

≡ p ∨ (!q ∨ r)

From here, use the commutative properties to rearrange the expression and apply the equivalence (of →) again to get the desired result.

**Related Questions**

Discrete math - Question: Use logical equivalnces to show that the propositions...

Discrete Mathematics - Let p and q be propositions. Use Logical equivalences to ...

3 grade math ms sue - 1-Explain how you can use a number line to show that 3/6 ...

math - Which statement is logically equivalent to ~a b? a ~b b ~a ~b...

Philosophy - First, translate the following statement pair into the symbols of ...

Math: Calculus - Assume that a population size at time t is N(t) and that N(t)=...

chemistry - This question I really don't get it. I tried tried tried to figure ...

Geometry - Which is logically equivalent to ~p -> q? a.) ~q -> p b.) ~q -&...

psy - Ms. Sue I need some data to help me discussed this question. How have you ...

Math 30 - A popular game show begins with the host reading a question to the ...